Using the 7-C Protocol to evaluate the Cape Winelands District Municipality's Climate Change Response Strategy's execution - Morrie, Ricardo Arthur (Stellenbosch : Stellenbosch University, 2025)
Thesis (MPA)--Stellenbosch University, 2024.